MRI in 31 patients with Behçet's disease and neurological involvement: prospective study with clinical correlation. Issue 7 (July 1993) - Wechsler, B; Dell'lsola, B; Vidailhet, M; Dormont, D; Piette, J C; Blétry, O; Godeau, P
Abstract : Thirty one patients with Behçet's disease and neurological manifestations were prospectively studied with MRI. Cerebral venous thrombosis was diagnosed in 10 patients. MRI performed during the acute illness in eight patients showed an abnormally high signal on the T2 weighted sequences in the occluded sinus. MRI showed minor flow abnormalities suggestive of partial recanalisation of the sinus in two cases at a later clinical stage. MRI can be an alternative, non-invasive, investigation to intravenous cerebral angiography. In 13 patients with central nervous system involvement, MRI performed during the acute illness showed multiple hyperintense lesions on T2 weighted sequences. They were usually less than 5 mm, scattered and confluent, mainly in the white matter, distributed in the hemispheric white matter in nine cases, brainstem in eight, basal ganglia and thalamus in five, and cortex in two. MRI abnormalities were usually associated with appropriate clinical deficits, but were larger and more disseminated than expected.